Rice cellulose synthase-like protein OsCSLD4 coordinates the trade-off between plant growth and defense - Liu, Xiong; Yin, Zhongliang; Wang, Yubo; Cao, Sai; Yao, Wei; Liu, Jinling; Lu, Xuedan; Wang, Feng; Zhang, Guilian; Xiao, Yunhua; Tang, Wenbang; Deng, Huabing (Frontiers in Plant Science, 2022)
Plant cell wall is a complex and changeable structure, which is very important for plant growth and development. It is clear that cell wall polysaccharide synthases have critical functions in rice growth and abiotic stress, yet their role in plant response to pathogen invasion is poorly understood. Here, we describe a dwarf and narrowed leaf in Hejiang 19 (dnl19) mutant in rice, which shows multiple growth defects such as reduced plant height, enlarged lamina joint angle, curled leaf morphology, and a decrease in panicle length and seed setting. MutMap analysis, genetic complementation and gene knockout mutant show that cellulose synthase-like D4 (OsCSLD4) is the causal gene for DNL19. Loss function of OsCSLD4 leads to a constitutive activation of defense response in rice. After inoculation with rice blast and bacterial blight, dnl19 displays an enhanced disease resistance. Widely targeted metabolomics analysis reveals that disruption of OsCSLD4 in dnl19 resulted in significant increase of L-valine, L-asparagine, L-histidine, L-alanine, gentisic acid, but significant decrease of L-aspartic acid, malic acid, 6-phosphogluconic acid, glucose 6-phosphate, galactose 1-phosphate, gluconic acid, D-aspartic acid. Collectively, our data reveals the importance of OsCSLD4 in balancing the trade-off between rice growth and defense.